Diabetic Wound Healing Activity of Anabas testudineus Fish Scales - Erwin Rosadi; Lia Yulia Budiarti; Bhisma Ridho Romadhon; Nida Nurkhalishah; Nur Salsabila Apriliani Risma Putri; Nur Azmina Aisyah; Isnaini Isnaini (Universitas Muhammadiyah Semarang, 2023)
Background: Anabas testudineus fish scales are part of the fish that has not been used optimally. Fish scales contain chitin. Chitin which undergoes deacetylation, produces chitosan. Chitosan is an efficacious compound for antibacterial and diabetic wound healing.Objective: This study aimed to extract chitosan from fish scales and test the diabetic wound healing activity of fish scale extract gelMethods: Extraction of fish scales using 0.3 M NaOH, 0.55 M HCl, and 50% NaOH. FTIR will analyze the extraction results to see the functional groups of the extract. Activity test of fish scale extracts diabetic wound healing gel was carried out on Rattus novergicus Wistar strain for 14 days. There were five treatments: negative control, positive control given octenillinR, and fish scale extract gel conc. 5%, 10%, and 15%.Results: The results showed that the fish scales extract contained chitosan, and gel extract fish scale conc 5% have diabetic wound healing activity better than 10% and 15%. Conclusion: A. testudineus fish scale extract contains chitosan, as seen from the FTIR results.